Quality vs Quantity: The Effect of Aristolochic Acids on Preference and Performance of a Non-Specialist Herbivore - Samantha Eileen Jeude (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
As immobile organisms, plants have evolved many strategies for defense against herbivores. These defenses can be physical, such as thorns, or chemical, such as antifeedant compounds. Most plants possess chemical compounds that serve a deterrent function against at least some herbivores. Aristolochic acids are alkaloids characteristic of plants of the genus Aristolochia. Although their toxicity and efficacy as herbivore deterrents have been documented, it is unknown whether different kinds of these compounds elicit different responses in herbivores. In this study, we use the generalist caterpillar Spodoptera exigua as a bioassay to evaluate both qualitative and quantitative effects of four aristolochic acids. Preference and performance were measured using artificial diets containing different aristolochic acids at different concentrations, all within the lower end of the natural range found in Aristolochia. We observed that some aristolochic acids (AAI and AAIII) were avoided at higher concentrations, while others (AAII and AA7-OH) had little or no effect on herbivore feeding patterns at any concentration. Performance tests were consistent with choice tests; those aristolochic acids that were stronger deterrents also had a stronger effect on larval growth. These results suggest consistent variation in the effectiveness of various aristolochic acids on both preference and performance.